Peningkatan Kualitas Kemasan Untuk Memperkuat Daya Saing Kripik Pare Kauman Mojokerto - Habsari, Nadiya; Alif Ibrahim, Daffa; Nasrudin, Muhammad (Fakultas Ekonomi Universitas Islam Majapahit, 2025)
The Thematic Community Service Program (KKN) in Kauman Village, Mojokerto City, was implemented to address the low competitiveness of SMEs due to competition with modern retail. This program focuses on improving the packaging quality of bitter melon chips (kripik pare) as a strategy to strengthen branding and product attractiveness. The implementation method uses the Business Model Canvas (BMC), which includes consumer segmentation, value proposition, distribution channels, customer relations, and digital marketing strategies. Activities carried out include SME data collection, socialization, packaging design training, and product rebranding. The results show increased interest from SMEs in adopting modern packaging designs, the creation of new packaging that is more hygienic and informative, and broader marketing through social media and e-commerce. This innovation is expected to become a model for empowering SMEs through packaging innovation to enhance local economic independence.